Characterization of adenine phosphoribosyltransferase (APRT) activity in Trypanosoma brucei brucei: Only one of the two isoforms is kinetically active. - Kayla Glockzin; Thomas D Meek; Ardala Katzfuss (Public Library of Science (PLoS), 2022)
Human African Trypanosomiasis (HAT), also known as sleeping sickness, is a Neglected Tropical Disease endemic to 36 African countries, with approximately 70 million people currently at risk for infection. Current therapeutics are suboptimal due to toxicity, adverse side effects, and emerging resistance. Thus, both effective and affordable treatments are urgently needed. The causative agent of HAT is the protozoan Trypanosoma brucei ssp. Annotation of its genome confirms previous observations that T. brucei is a purine auxotroph. Incapable of de novo purine synthesis, these protozoan parasites rely on purine phosphoribosyltransferases to salvage purines from their hosts for the synthesis of purine monophosphates. Complete and accurate genome annotations in combination with the identification and characterization of the catalytic activity of purine salvage enzymes enables the development of target-specific therapies in addition to providing a deeper understanding of purine metabolism in T. brucei. In trypanosomes, purine phosphoribosyltransferases represent promising drug targets due to their essential and central role in purine salvage. Enzymes involved in adenine and adenosine salvage, such as adenine phosphoribosyltransferases (APRTs, EC 2.4.2.7), are of particular interest for their potential role in the activation of adenine and adenosine-based pro-drugs. Analysis of the T. brucei genome shows two putative aprt genes: APRT1 (Tb927.7.1780) and APRT2 (Tb927.7.1790). Here we report studies of the catalytic activity of each putative APRT, revealing that of the two T. brucei putative APRTs, only APRT1 is kinetically active, thereby signifying a genomic misannotation of Tb927.7.1790 (putative APRT2). Reliable genome annotation is necessary to establish potential drug targets and identify enzymes involved in adenine and adenosine-based pro-drug activation.